Welding process for brazing sapphire by adopting novel glass

Through the new glass brazing process, glass solder paste is prepared using raw materials such as bismuth oxide, boron oxide, and silicon oxide, which solves the problem of mechanical performance reduction in the existing sapphire brazing process, and achieves good mechanical properties and long-term service stability of the weld.

CN119612966AActive Publication Date: 2025-03-14NORTHWESTERN POLYTECHNICAL UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411798692.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The existing sapphire brazing process leads to a decrease in mechanical properties, mainly due to the formation of brittle intermetallic compounds caused by metal brazing and the residual stress caused by the difference in thermal expansion coefficient between ceramics and metals.

Method used

Using the new glass brazing process, glass powder is prepared by ball milling and mixing raw materials such as bismuth oxide, boron oxide, silicon oxide in a specific proportion, and mixing it with butyl acetate to form glass solder paste. Brazing is carried out through the sandwich structure to reduce thermal stress and improve interface bonding force.

Benefits of technology

The good mechanical properties and long-term service stability of the weld are achieved, the thermal stress caused by the difference in thermal expansion coefficient is reduced, and the mechanical properties and connection quality of the joint are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612966A_ABST
    Figure CN119612966A_ABST
Patent Text Reader

Abstract

The invention discloses a welding process adopting novel glass to braze sapphire, and particularly relates to the field of sapphire brazing. Comprising the following steps: ball-milling and mixing bismuth oxide powder, boron oxide powder and silicon oxide powder to obtain a mixture; heating the mixture to obtain molten glass liquid; pouring the molten glass into cold water to obtain glass particles; carrying out ball milling on the glass particles to obtain glass powder; glass powder and a binder are mixed, and glass soldering paste is obtained; the surface of the sapphire is coated with glass soldering paste, and a sapphire-glass soldering paste-sapphire sandwich structure is formed; and the interlayer structure is heated to the brazing temperature, and the welded sapphire is obtained. Thermal stress generated by anisotropy of thermal expansion coefficient of sapphire base metal can be reduced, so that a welding seam has good mechanical property and long-term service stability, and the connecting welding seam is narrow and high in strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sapphire brazing, and in particular to a welding process for brazing sapphire using a new type of glass. Background Art

[0002] Sapphire is a modern structural material with good conductivity, mechanical strength and high temperature resistance. It has a wide range of uses and has broad application prospects in the fields of aerospace, automobiles, chemicals and nuclear energy. However, since sapphire is a compound mainly bonded by covalent bonds, its inherent brittleness makes it very difficult to prepare large and complex parts. Therefore, it is usually necessary to use the connection technology between sapphires to make these parts.

[0003] The connection process of sapphire materials mainly needs to solve two problems: one is the wettability problem of the connection interface; the other is the stress buffering problem of the joint. At present, there are many process methods for connecting sapphire, such as diffusion connection, mechanical connection, physical and chemical vapor deposition connection and brazing. Among them, brazing has the advantages of simple process, low equipment investment and suitability for production requirements. At present, the brazing connection of sapphire mainly uses specific active brazing filler metals to achieve the connection. However, the use of metal brazing filler metals to braze ceramic joints is prone to generate continuous brittle intermetallic compounds, which will reduce the connection quality of the joint. In addition, the linear expansion coefficients of ceramics and metals are quite different, and large residual stress will be generated at the joint, reducing the mechanical properties of the joint. Summary of the invention

[0004] The main purpose of the present application is to provide a welding process for sapphire brazing using a new glass, aiming to solve the problem that the existing brazing of sapphire causes its mechanical properties to deteriorate.

[0005] To achieve the above-mentioned purpose, the present application provides a glass powder, the raw materials of the glass powder include bismuth oxide, boron oxide, and silicon oxide, and the mass ratio of bismuth oxide, boron oxide, and silicon oxide is 5:4:(1-2).

[0006] To achieve the above-mentioned purpose, the present application also provides a method for preparing the above-mentioned glass powder, comprising: ball-milling bismuth oxide powder, boron oxide powder, and silicon oxide powder in a mass ratio of 5:4:(1-2) to obtain a mixture; heating the mixture to obtain a molten glass liquid; pouring the glass liquid into cold water to obtain glass particles; and ball-milling the glass particles to obtain glass powder.

[0007] Optionally, the ball milling mixing is performed in a ball mill, the rotation speed of the ball mill is 600-800 rpm, and the ball milling time is 5-6 hours.

[0008] Optionally, during the heating process, the temperature is raised to 1000° C. at a rate of 5-10° C. / min and maintained for 1-2 hours.

[0009] To achieve the above objectives, the present application also provides an application of the above glass powder in brazing sapphire.

[0010] To achieve the above-mentioned purpose, the present application also provides a welding process for brazing sapphire with a new type of glass, comprising: mixing the above-mentioned glass powder and butyl acetate to obtain a glass solder paste; coating the glass solder paste on the surface of the sapphire to form a sandwich structure of sapphire-glass solder paste-sapphire; heating the sandwich structure to 300°C, keeping it at this temperature for 10 minutes, and continuing to heat it to the brazing temperature to obtain the welded sapphire.

[0011] The mass ratio of glass powder to binder is 5:0.3-0.6.

[0012] The binder is pineol.

[0013] The rate during the heating process is 5°C / min, and the brazing temperature is 550°C-650°C.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The welding process of brazing sapphire with a novel glass is disclosed. The solder paste prepared from the above-mentioned glass powder is used as the solder for brazing, which can reduce the thermal stress caused by the anisotropic thermal expansion coefficient of the sapphire base material, so that the weld has good mechanical properties and long-term service stability, and the connection weld is narrow and has high strength. The glass powder obtained in the present application can wet the ceramic interface well, reduce the joint stress formed, and the joint connection quality is high, and the mechanical properties of the joint are improved. The process is relatively simple, the equipment investment is low, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is an electron microscope image of a sample obtained in Example 1 of the present application using a new glass brazing sapphire welding process.

[0016] Figure 2 This is a whisker precipitation diagram of the sample obtained in Example 1 of the present application using a new glass brazing sapphire welding process.

[0017] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0019] A first embodiment of the present invention provides a glass powder. The raw materials of the glass powder include bismuth oxide, boron oxide, and silicon oxide. The mass ratio of bismuth oxide, boron oxide, and silicon oxide is 5:4:(1-2).

[0020] The glass powder of the present invention uses bismuth oxide, boron oxide and silicon oxide as raw materials and Bi2O3 as a flux, which can reduce the melting temperature and viscosity of the glass powder, promote the melting and flow of the glass powder, make the solder fill the weld better during the welding process, and improve the chemical stability; improve the chemical stability of the glass powder, reduce the possibility of chemical reaction with sapphire and the surrounding environment during the brazing process, and help to ensure the stability and reliability of the welded joint. At the same time, it also helps to reduce the thermal expansion coefficient of the glass powder, make it more compatible with the thermal expansion coefficient of sapphire, reduce the thermal stress generated by the difference in thermal expansion coefficient during the welding process, and avoid defects such as cracks in the welded joint. SiO2 has high chemical and thermal stability, which can improve the overall stability of glass powder, making it less likely to decompose and deteriorate during high-temperature brazing, thus ensuring the smooth progress of the brazing process; it can also adjust the viscosity of glass powder so that the brazing material has appropriate fluidity and viscosity after melting, which is beneficial for filling the weld and preventing excessive flow of the brazing material, thereby obtaining a good welding shape and dimensional accuracy; during the brazing process, SiO2 can undergo a certain chemical reaction with the sapphire surface to form a chemical bond, thereby enhancing the interfacial bonding force between the brazing material and sapphire and improving the strength and reliability of the welded joint.

[0021] Bi203, B2O3, and SiO2 work together to significantly reduce the melting point and viscosity of glass powder, so that it can form a liquid solder with good fluidity at a lower temperature, which is easy to spread and wet on the sapphire surface, providing the prerequisite for achieving high-quality brazing. The addition of B2O3 and SiO2 helps to adjust the thermal expansion coefficient of glass powder, making it closer to the thermal expansion coefficient of sapphire and reducing the generation of thermal stress. At the same time, the low melting point characteristics of Bi203 also help to reduce the temperature gradient during brazing, further relieve thermal stress, and thus improve the stability and reliability of the welded joint. Bi203 and B2O3 improve the wettability of the solder, so that SiO2 can better contact and react with the sapphire surface to form a strong chemical bond. The synergistic effect of the three greatly enhances the interfacial bonding between the solder and sapphire, and improves the strength and quality of the welded joint. And it can wet the sapphire interface well and reduce joint stress.

[0022] A second embodiment of the present invention provides a method for preparing the above-mentioned glass powder, which specifically comprises the following steps: Step S1, placing bismuth oxide powder, boron oxide powder and silicon oxide powder in a planetary ball mill according to a mass ratio of 5:4:(1-2), and ball milling them at a rotation speed of 600-800 rpm for 5-6 hours to obtain a mixture; Step S2, pouring the mixture into a platinum crucible, heating it to 1000° C. at a rate of 5-10° C. / min, and keeping it warm for 1-2 hours to obtain molten glass liquid; Step S3, pouring the glass liquid into cold water to obtain glass particles, and ball-milling the glass particles to obtain glass powder.

[0023] The third embodiment of the present invention provides a welding process for sapphire using a novel glass brazing method, which specifically includes the following steps: Step S4, mixing glass powder and pinene alcohol in a mass ratio of 5:0.3-0.6 to obtain a glass solder paste; Step S5, coating the glass solder paste on the sapphire surface to form a sandwich structure of sapphire-glass solder paste-sapphire; Step S6, heating the sandwich structure to 300°C at a rate of 5°C / min, and keeping it at this temperature for 10 minutes to burn out the organic components. This is done to allow the solder to fully and evenly melt and flow, so as to better fill the weld; secondly, to make the temperature of each part of the weld uniform, reduce thermal stress, avoid defects such as cracks, and thus improve the welding quality; and continue to heat up to 550°C-650°C at a rate of 5°C / min, and the sample is cooled to room temperature with the furnace to obtain the welded sapphire.

[0024] In this embodiment, the glass powder is used to prepare a solder paste as the solder for brazing. The solder paste achieves excellent wetting and casting between the sapphires and completely fills the gaps between the sapphires. Therefore, the formed joint is very uniform, and no defects such as slag inclusions and pores can be observed with the naked eye. This ensures a good connection effect, improves the strength and sealing of the joint, and ensures the mechanical properties of the sapphire.

[0025] Example 1 Step S1, placing Bi2O3, B2O3, and SiO2 in a planetary ball mill for ball milling at a mass ratio of 5:4:1, and ball milling at a rotation speed of 600 rpm for 5 hours to obtain a mixture; Step S2, pouring the mixture into a platinum crucible, heating it to 1000° C. at a rate of 5° C. / min, and keeping the temperature for 1 hour to obtain molten glass liquid; Step S3, pouring the glass liquid into cold water to obtain 3 mm glass particles, and ball milling the glass particles (size) to obtain glass powder; Step S4, mixing glass powder and pinene alcohol in a mass ratio of 5:0.3 to obtain a glass solder paste; Step S5, coating the glass solder paste on the sapphire surface to form a sandwich structure of sapphire-glass solder paste-sapphire; Step S6, heating the sandwich structure to 300°C at a rate of 5°C / min, keeping it at this temperature for 10 minutes, and continuing to heat it to 550°C at a rate of 5°C / min. The sample is cooled to room temperature with the furnace to obtain the welded sapphire, i.e., the brazing sample.

[0026] The performance of the sapphire obtained after welding in this embodiment was tested, and the results are as follows.

[0027] The thermal expansion coefficient of the glass powder was evaluated using a dilatometer and was found to be 9.3 × 10 -6 / °C.

[0028] The microstructure and fracture surface of the brazed samples were examined using a scanning electron microscope equipped with an Oxford energy dispersive X-ray analysis system. Figure 1 As shown in the figure, it can be seen that the glass powder (new glass) obtained in this embodiment achieves excellent wetting and casting between sapphires, completely filling the gaps between sapphires. The joints formed thereby are very uniform, and no defects such as slag inclusions and pores can be observed with the naked eye.

[0029] Transmission electron microscopy with a super-XEDS system was used to further characterize and identify the precipitated whisker phase in the brazed joint. Figure 2 As shown in the figure, during the brazing process, whisker phase is generated at the joint. Under appropriate conditions, this type of beneficial precipitation phase can enhance the joint performance.

[0030] In air, the dimensions are 6×6×3 mm 3 The wetting test of glass particles was carried out, and the wetting angle was 116.7 。

[0031] At this temperature, the wetting angle is still large, indicating good wettability between glass and sapphire.

[0032] Helios Nanolab 600i was used to prepare TEM samples consisting of three 12*6 sapphire samples with the same bottom, covered with a new glass powder composed of Bi203, B203, and Si02 in the middle, and a 6*6 sapphire sample on the top by using focused ion beam technology (FIB) at a heating rate of 10℃ / min. The brazing sample was heated from room temperature to 550℃. The shear strength of the TEM sample joint was measured using a TMST universal testing machine at a constant speed of 0.5 mm / min, and the average shear strength of the brazed joint was calculated to be 50MPa.

[0033] After the shear test, the shear fracture surface was checked using SEM, and it was found that the shear fracture surface was relatively flat and smooth. This shows that during the brazing process, the glass and sapphire achieved a good bond, and the stress distribution was relatively uniform. There was no rough, uneven fracture caused by loose bonding or excessive internal stress concentration. The overall structure was able to maintain a relatively stable state until it broke when subjected to shear force, which indirectly reflects the reliable connection quality between the two.

[0034] Comparative Example 1 Using Bi2O3 and B2O3 as raw materials, according to steps S1-S6, a brazing sample is obtained. A TEM sample is also prepared, and the average shear strength of the TEM sample joint is 47 MPa.

[0035] Example 2 Step S1, placing Bi2O3, B2O3, and SiO2 in a planetary ball mill for ball milling at a mass ratio of 5:4:1.2, and ball milling at a rotation speed of 650 rpm for 5 h to obtain a mixture; Step S2, pouring the mixture into a platinum crucible, heating it to 1000° C. at a rate of 6° C. / min, and keeping the temperature for 1.2 hours to obtain molten glass liquid; Step S3, pouring the glass liquid into cold water to obtain glass particles of 3 mm in size, and ball milling the glass particles (size) to obtain glass powder; Step S4, mixing glass powder and pinene alcohol in a mass ratio of 5:0.3 to obtain a glass solder paste; Step S5, coating the glass solder paste on the sapphire surface to form a sandwich structure of sapphire-glass solder paste-sapphire; Step S6, heating the sandwich structure to 300°C at a rate of 5°C / min, keeping it at this temperature for 10 minutes, and continuing to heat it to 575°C at a rate of 5°C / min. The sample is cooled to room temperature in the furnace to obtain the welded sapphire, i.e., the brazing sample.

[0036] The performance of the sapphire obtained after welding in this embodiment was tested, and the results are as follows.

[0037] The thermal expansion coefficient of the glass powder was evaluated using a dilatometer and was 8.4 × 10 -6 / °C.

[0038] In air, the dimensions are 6×6×3 mm 3 The wetting test of glass particles was carried out, and the wetting angle was 68.7 。

[0039] At this temperature, the wetting angle is still large, indicating good wettability between glass and sapphire.

[0040] Helios Nanolab 600i was used to prepare TEM samples consisting of three 12*6 sapphire samples with the same bottom, covered with a new glass powder composed of Bi203, B203, and Si02 in the middle, and a 6*6 sapphire sample on the top by using focused ion beam technology (FIB) at a heating rate of 10℃ / min. The brazing sample was heated from room temperature to 575℃. The shear strength of the TEM sample joint was measured using a TMST universal testing machine at a constant speed of 0.5 mm / min, and the average shear strength of the brazed joint was calculated to be 60MPa.

[0041] After the shear test, the shear fracture surface was checked using SEM, and it was found that the shear fracture surface was relatively flat and smooth. This shows that during the brazing process, the glass and sapphire achieved a good bond, and the stress distribution was relatively uniform. There was no rough, uneven fracture caused by loose bonding or excessive internal stress concentration. The overall structure was able to maintain a relatively stable state until it broke when subjected to shear force, which indirectly reflects the reliable connection quality between the two.

[0042] Comparative Example 2 Using Bi2O3 and B2O3 as raw materials, according to steps S1-S6, a brazing sample is obtained. A TEM sample is also prepared, and the average shear strength of the TEM sample joint is 54 MPa.

[0043] Example 3 Step S1, placing Bi2O3, B2O3, and SiO2 in a planetary ball mill for ball milling and mixing at a mass ratio of 5:4:1.4, and ball milling at a rotation speed of 700 rpm for 5.5 hours to obtain a mixture; Step S2, pouring the mixture into a platinum crucible, heating it to 1000° C. at a rate of 5-10° C. / min, and keeping the temperature for 2 hours to obtain molten glass liquid; Step S3, pouring the glass liquid into cold water to obtain glass particles of 4 mm in size, and ball milling the glass particles (size) to obtain glass powder; Step S4, mixing glass powder and pinene alcohol in a mass ratio of 5:0.4 to obtain a glass solder paste; Step S5, coating the glass solder paste on the sapphire surface to form a sandwich structure of sapphire-glass solder paste-sapphire; Step S6, heating the sandwich structure to 300°C at a rate of 5°C / min, keeping it at this temperature for 10 minutes, and continuing to heat it to 600°C at a rate of 5°C / min. The sample is cooled to room temperature in the furnace to obtain the welded sapphire, i.e., the brazing sample.

[0044] The performance of the sapphire obtained after welding in this embodiment was tested, and the results are as follows.

[0045] The thermal expansion coefficient of the glass powder was evaluated using a dilatometer and was 7.8× 10 -6 / °C.

[0046] In air, the dimensions are 6×6×3 mm 3 The wetting test of glass particles was carried out, and the wetting angle was 43.2 。

[0047] At this temperature, the wetting angle is still large, indicating good wettability between glass and sapphire.

[0048] Helios Nanolab 600i was used to prepare TEM samples consisting of three 12*6 sapphire samples with the same bottom at a heating rate of 10℃ / min by focused ion beam technology (FIB) from room temperature to 600℃. The middle was covered with a new glass powder composed of Bi203, B203, and Si02, and the upper part was a 6*6 sapphire sample. The shear strength of the TEM sample joint was measured using a TMST universal testing machine at a constant speed of 0.5 mm / min, and the average shear strength of the brazed joint was calculated to be 75MPa.

[0049] After the shear test, the shear fracture surface was checked using SEM, and it was found that the shear fracture surface was relatively flat and smooth. This shows that during the brazing process, the glass and sapphire achieved a good bond, and the stress distribution was relatively uniform. There was no rough, uneven fracture caused by loose bonding or excessive internal stress concentration. The overall structure was able to maintain a relatively stable state until it broke when subjected to shear force, which indirectly reflects the reliable connection quality between the two.

[0050] Comparative Example 3 Using Bi2O3 and B2O3 as raw materials, according to steps S1-S6, a brazing sample is obtained. A TEM sample is also prepared, and the average shear strength of the TEM sample joint is 68 MPa.

[0051] Example 4 Step S1, placing Bi2O3, B2O3, and SiO2 in a planetary ball mill for ball milling at a mass ratio of 5:4:1.6, and ball milling at a rotation speed of 800 rpm for 6 hours to obtain a mixture; Step S2, pouring the mixture into a platinum crucible, heating it to 1000° C. at a rate of 10° C. / min, and keeping the temperature for 2 hours to obtain molten glass liquid; Step S3, pouring the glass liquid into cold water to obtain glass particles of 4 mm in size, and ball milling the glass particles (size) to obtain glass powder; Step S4, mixing glass powder and pinene alcohol in a mass ratio of 5:0.4 to obtain a glass solder paste; Step S5, coating the glass solder paste on the sapphire surface to form a sandwich structure of sapphire-glass solder paste-sapphire; Step S6, heating the sandwich structure to 300°C at a rate of 5°C / min, keeping it at this temperature for 10 minutes, and continuing to heat it to 625°C at a rate of 5°C / min. The sample is cooled to room temperature in the furnace to obtain the welded sapphire, i.e., the brazing sample.

[0052] The performance of the sapphire obtained after welding in this embodiment was tested, and the results are as follows.

[0053] The thermal expansion coefficient of the glass powder was evaluated using a dilatometer and was 6.8× 10 -6 / °C.

[0054] In air, the dimensions are 6×6×3 mm 3 The wetting test of glass particles was carried out, and the wetting angle was 23.1 。

[0055] At this temperature, the wetting angle is still large, indicating good wettability between glass and sapphire.

[0056] Using Helios Nanolab 600i, focused ion beam technology (FIB) was used to heat the brazed sample from room temperature to 625°C at a heating rate of 10°C / min. Three 12*6 sapphire samples with the same bottom were prepared. The middle was covered with a new glass powder composed of Bi203, B203, and Si02, and the upper part was composed of 6*6 sapphire samples. TEM samples were used for mechanical property testing. The shear strength of the joint was measured using a TMST universal testing machine at a constant speed of 0.5 mm / min, and the average shear strength of the brazed joint was calculated to be 70MPa.

[0057] After the shear test, the shear fracture surface was checked using SEM, and it was found that the shear fracture surface was relatively flat and smooth. This shows that during the brazing process, the glass and sapphire achieved a good bond, and the stress distribution was relatively uniform. There was no rough, uneven fracture caused by loose bonding or excessive internal stress concentration. The overall structure was able to maintain a relatively stable state until it broke when subjected to shear force, which indirectly reflects the reliable connection quality between the two.

[0058] Comparative Example 4 Using Bi2O3 and B2O3 as raw materials, according to steps S1-S6, a brazing sample is obtained. A TEM sample is also prepared, and the average shear strength of the TEM sample joint is 59 MPa.

[0059] Example 5 Step S1, placing Bi2O3, B2O3, and SiO2 in a planetary ball mill for ball milling at a mass ratio of 5:4:2, and ball milling at a rotation speed of 800 rpm for 6 hours to obtain a mixture; Step S2, pouring the mixture into a platinum crucible, heating it to 1000° C. at a rate of 10° C. / min, and keeping it warm for 1-2 hours to obtain molten glass liquid; Step S3, pouring the glass liquid into cold water to obtain glass particles of 4 mm in size, and ball milling the glass particles (size) to obtain glass powder; Step S4, mixing glass powder and pinene alcohol in a mass ratio of 5:0.4 to obtain a glass solder paste; Step S5, coating the glass solder paste on the sapphire surface to form a sandwich structure of sapphire-glass solder paste-sapphire; Step S6, heating the sandwich structure to 300°C at a rate of 5°C / min, keeping it at this temperature for 10 minutes, and continuing to heat it to 650°C at a rate of 5°C / min. The sample is cooled to room temperature in the furnace to obtain the welded sapphire, i.e., the brazing sample.

[0060] The performance of the sapphire obtained after welding in this embodiment was tested, and the results are as follows.

[0061] The thermal expansion coefficient of the glass powder was evaluated using a dilatometer and was 5.9× 10 -6 / °C.

[0062] In air, the dimensions are 6×6×3 mm 3 The wetting test of glass particles was carried out, and the wetting angle was 11.7 。

[0063] At this temperature, the wetting angle is still large, indicating good wettability between glass and sapphire.

[0064] Helios Nanolab 600i was used to prepare TEM samples consisting of three 12*6 sapphire samples with the same bottom, covered with a new glass powder composed of Bi203, B203, and Si02 in the middle, and a 6*6 sapphire sample on the top by using focused ion beam technology (FIB) at a heating rate of 10℃ / min. The brazing sample was heated from room temperature to 650℃. The shear strength of the TEM sample joint was measured using a TMST universal testing machine at a constant speed of 0.5 mm / min, and the average shear strength of the brazed joint was calculated to be 65MPa.

[0065] After the shear test, the shear fracture surface was checked using SEM, and it was found that the shear fracture surface was relatively flat and smooth. This shows that during the brazing process, the glass and sapphire achieved a good bond, and the stress distribution was relatively uniform. There was no rough, uneven fracture caused by loose bonding or excessive internal stress concentration. The overall structure was able to maintain a relatively stable state until it broke when subjected to shear force, which indirectly reflects the reliable connection quality between the two.

[0066] Comparative Example 5 Using Bi2O3 and B2O3 as raw materials, according to steps S1-S6, a brazing sample is obtained. A TEM sample is also prepared, and the average shear strength of the TEM sample joint is 47 MPa.

[0067] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A glass powder, characterized in that: The raw materials of the glass powder include bismuth oxide, boron oxide and silicon oxide, wherein the mass ratio of the bismuth oxide, boron oxide and silicon oxide is 5:4:(1-2).

2. A method for preparing the glass powder according to claim 1, characterized in that: include: Bismuth oxide powder, boron oxide powder, and silicon oxide powder are ball-milled and mixed in a mass ratio of 5:4:(1-2) to obtain a mixture; Heating the mixture to obtain molten glass; pouring the glass liquid into cold water to obtain glass particles; The glass particles are ball-milled to obtain glass powder.

3. The method for preparing glass powder according to claim 2, characterized in that: The ball milling mixing is carried out in a ball mill, the rotation speed of the ball mill is 600-800 rpm, and the ball milling time is 5-6 hours.

4. The method for preparing glass powder according to claim 2, characterized in that: During the heating process, the temperature is raised to 1000° C. at a rate of 5-10° C. / min and maintained for 1-2 hours.

5. Use of the glass powder as claimed in claim 1 in brazing sapphire.

6. A new type of glass brazing sapphire welding process, characterized in that: include: Mixing the glass powder according to claim 1 and butyl acetate to obtain a glass solder paste; Applying the glass solder paste on the surface of sapphire to form a sandwich structure of sapphire-glass solder paste-sapphire; The sandwich structure is heated to 300° C., kept at this temperature for 10 minutes, and then further heated to the brazing temperature to obtain the welded sapphire.

7. The welding process of using a new type of glass brazing sapphire according to claim 6 is characterized in that: The mass ratio of the glass powder to the binder is 5:0.3-0.

6.

8. The novel glass brazing sapphire welding process according to claim 6 is characterized in that: The binder is terpineol.

9. The novel glass brazing sapphire welding process according to claim 6, characterized in that: The rate during the heating process is 5°C / min, and the brazing temperature is 550°C-650°C.

Citation Information

Patent Citations

  • Low-temperature welding method for sapphires

    CN105364245A

  • Processing technology of sapphire glass component

    CN107414228A

  • Diffusion welding connection method for sapphire

    CN112958901A

  • Low-melting-point sealing glass powder

    CN116332511A

  • Sapphire circular tube sealing structure

    CN214115778U